Effect of bacterial aggregation on the adherence of oral streptococci to hydroxyapatite. - Liljemark, W F (1981)
Several in vitro assay systems to measure the adherence of human dental plaque bacteria to solid surfaces such as teeth, glass, and hydroxyapatite have been published. In many studies a variety of macromolecular solutes have been used to study the adherence process. Often these solutes are able to aggregate the test bacterial and thus may alter the outcome of adherence experiments. In this study, the effects of the aggregation of Streptococcus sanguis on adherence to spheroidal hydroxyapatite is described. Adherence of preformed aggregates and of bacteria which were aggregating during the adherence reaction was examined. Bacteria were aggregated with whole saliva, concanavalin A, and wheat germ lectin. Further effects of the coaggregation of S. mitis and Actinomyces viscosus to saliva-coated spheroidal hydroxyapatite are presented. These studies suggest that formation of large aggregates resulted in a decrease in the numbers of organisms which adhered. In contrast, the formation of small aggregates actually increased the numbers of bacteria that adhered. All increases in adherent bacteria occurred at low concentrations of aggregating substance in which visible bacterial aggregation was not evident. The data indicate that adequate dose-response experiments must be performed to ensure that solutes used as probes to study adherence mechanisms do not affect the adherence simply as a result of aggregation of the test microorganisms.